Quality and sulfur residues of raisin made after sulfur fumigation at different time intervals - Iqbal, Mujahid; Khan, Abdul Rahim; Iqbal, Majid; Ahmed, Jahangir (Journal of Postharvest Technology, 2024)
The grape berries were exposed to the sulfur fumes for 0, 20, 30, and 40 minutes to make raisin and it was found that for the entire organoleptic characters raisin made after 30 minutes of sulfur fumigation showed the best results for all characters of quality. The 30 minutes fumigation for raisin making was highest for taste, color, flavor, and texture compared to control, 20 and 40 minutes fumigation. The weight remain percentage was highest for 30 and 40 minutes fumigated and lowest for the control berries of raisin. It was noticed that the sulfur residues increased with the increased in sulfur fumigation time. The 20, 30 and 40 minutes fumigated raisins came under permissible residues of SO2 for all the treatments. These results suggest that 30 minutes fumigation gave better results and therefore could be recommended for raisin making for future.